Un análisis bibliométrico en el área de la Medicina: colaboración científica entre Brasil y España (2002-2011) - Alonso Arroyo, Adolfo; de Oliveira, Ely Francina Tannuri [UNESP]; Cabrini Grácio, Maria Cláudia [UNESP]; Pandiella, Andrés; Aleixandre Benavent, Rafael (Universidad Nacional Autonoma de Mexico, 2016)
This study analyzes the development of Spanish-Brazilian collaborative scientific production in the field of medical research between 2002 and 2011, identifying the most productive institutions, the proportion of researchers from each country and bi-lateral collaborative networks. Data were gathered from the Scopus database, which offers broad, international coverage of multidisciplinary research. A study sample of 1,121 original scientific articles signed by 13,906 researchers were retrieved, on the basis of which the annual growth rate of Spanish-Brazilian medical research was calculated. A remarkably high degree of internationalization was found, with 121 countries participating in the papers sampled. Moreover, Fully 51 countries in this international network boast at least 15 contributions. The study finds a high degree of collaboration between Spain and Brazil, and significant growth of collaboration in the area of medical research, including collaborations with other countries, with fully 58% of the sample involving a third country.
A bibliometric analysis of collaboration between Brazil and Spain in the field of medical research from 2002 to 2011
Keywords: Brazil; Collaboration networks; Medicine; scientific collaboration; Spain